2014
DOI: 10.5530/jyp.2014.3.3
|View full text |Cite
|
Sign up to set email alerts
|

Minimizing pharmaceutical waste: The role of the pharmacist

Abstract: Leftover and expired drugs, an indirect measure of wasted healthcare resources, reflect lost opportunities to achieve therapeutic outcomes (either due to incorrect choice or noncompliance) and a burden for the environment. In addition, medication waste is costly to national health systems because The questionnaire assessed disposal of leftover and expired drugs by pharmacists and their knowledge of drug disposal by the distributors. The awareness of the correct method of drug disposal, ways to minimize the pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 11 publications
2
16
0
3
Order By: Relevance
“…Forty percent of those surveyed disposed of expired medications in an unsustainable way (ie, flush down toilet, place with biohazardous materials), and 21% surveyed did not know how expired medications were disposed of. This is similar to the findings of a 2014 study 25 in which 37% of pharmacists surveyed were unsure how pharmaceutical distributors disposed of medications. Returning expired medications to drug distributors was the most common route of disposal for pharmacists.…”
Section: Disposal Of Medicationssupporting
confidence: 87%
“…Forty percent of those surveyed disposed of expired medications in an unsustainable way (ie, flush down toilet, place with biohazardous materials), and 21% surveyed did not know how expired medications were disposed of. This is similar to the findings of a 2014 study 25 in which 37% of pharmacists surveyed were unsure how pharmaceutical distributors disposed of medications. Returning expired medications to drug distributors was the most common route of disposal for pharmacists.…”
Section: Disposal Of Medicationssupporting
confidence: 87%
“…It is observed that pharmacy students' and pharmacists' attitudes are commonly used by researchers in several studies about pharmacy practice and education. [63][64][65][66][67] In addition, findings of this study are parallel to the literature about partnership and other types of business collaborations, too. 17,18,45,46 In this regard, both of H 1 and H 2 hypotheses are supported by the literature.…”
Section: Discussion Of the Structural Equation Model Resultssupporting
confidence: 68%
“…Therefore, a standardized, 20-items, self-administered questionnaire designed and developed to evaluate pharmacist knowledge when generating pharmaceutical waste in pharmacies. The questionnaire was developed depending on information drawn from the literature, and a number of questions were adapted and modified from other studies regarding pharmacist knowledge on drug disposal and its effect on health and environment [1,12,13,14,15,16,17,18]. Validation was performed to determine whether the study tool measured the intended goal of this study.…”
Section: Methodsmentioning
confidence: 99%